2008
DOI: 10.1007/s11064-008-9733-6
|View full text |Cite
|
Sign up to set email alerts
|

Mu-Opioid Receptor in the Nucleus Submedius: Involvement in Opioid-Induced Inhibition of Mirror-Image Allodynia in a Rat Model of Neuropathic Pain

Abstract: The current study investigated the roles of various subtypes of opioid receptors expressed in the thalamic nucleus submedius (Sm) in inhibition of mirror-image allodynia induced by L5/L6 spinal nerve ligation in rats. Morphine was microinjected into the Sm, which produced a dose-dependent inhibition of mirror-image allodynia; this effect was antagonized by pretreatment with non-selective opioid receptor antagonist naloxone. Microinjections of endomorphin-1 (mu-receptor agonist), or [D-Ala(2), D-Leu(5)]-enkepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Variation in the development of contralateral hypersensitivity has also been reported in the SNI model [13,14]. It has been proposed that such mirror-image sensitisation may be subject to regulation by endogenous analgesic mechanisms [59], and this suppression can be mimicked by the systemic administration of the α 2 -agonist clonidine [67]. We have extended these findings to show that mirror-image sensitisation can be uncovered by blocking descending NAergic tone indicating that these pontospinal neurons are actively opposing the spread of sensitisation at a spinal level.…”
Section: Discussionmentioning
confidence: 88%
“…Variation in the development of contralateral hypersensitivity has also been reported in the SNI model [13,14]. It has been proposed that such mirror-image sensitisation may be subject to regulation by endogenous analgesic mechanisms [59], and this suppression can be mimicked by the systemic administration of the α 2 -agonist clonidine [67]. We have extended these findings to show that mirror-image sensitisation can be uncovered by blocking descending NAergic tone indicating that these pontospinal neurons are actively opposing the spread of sensitisation at a spinal level.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, others suggested that supraspinal structures may play important roles in the occurrence of mirror pain. For instance, the opioid receptor signaling in the thalamic submedius and ventromedial nuclei are inhibitory of mirror or contralateral pain whereas the mediodorsal (MD) nucleus, a key relay for spinal nociceptive inputs [ 23 ], facilitates the mirror or contralateral pain [ 6 , 24 , 25 ]. The anterior cingulate cortex (ACC) is a first-order cortical region that responds to painful stimuli [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…We expected that the nerve injury evoked disappearance of latexin in spinal cord neurons should increase carboxypeptidase A activity and possibly enhance protein breakdown of carboxypeptidase substrate proteins or peptides. Among them are the endogenous opiod leu-enkephalin [32] and endothelin-1 [33] which may impact on the endogenous ability of nociceptive control [34], [35]. Increased cleavage particularly of endogenous opioid peptides might contribute to the development of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%